The Implementation of Arabic E-Learning through Arabic-Online.net - Mardliyyah, Aisyam (IAIN Salatiga, 2020)
This study aims to describe Arabic-Online.net and to find out how it is used in the implementation of Arabic learning. Applying a qualitative approach, this research was of literature study. The main object is e-learning site i.e. Arabic-Online.net which can be accessed openly to learn Arabic. Further, this study found that Arabic-Online.net is an Arabic learning model provided to non-native speakers, which is offered by the Saudi Electronic University. Its teaching is based on the General European reference framework by using four language skills and the main components in Arabic. There are 16 levels in the stages ranging from beginner, elementary, intermediate, upper intermediate, advanced, to mastery which contain as many as 796 main interactive videos, 12.000 audio files, 6.320 images and 10.076 exercises. Each level consists of 6 modules (units), each of which includes 24 lessons. E-learning implementation using Arabic-Online.net is conducted in the form of blended learning.